Dry mouth. (2nd October 2021) - Nayee, Shalini; Herbert, Cameron; Shirlaw, Pepe; Cook, Richard
Abstract : Dry mouth has numerous causes, including medications, radiotherapy and rheumatological conditions, such as Sjögren's syndrome. This article presents the common causes of dry mouth, and details the assessment, investigations and management required for patients with dry mouth within primary dental care, in addition to outlining secondary care investigations and management. CPD/Clinical Relevance : Dry mouth is common in the general population, with widespread implications for dental health and patients' quality of life. Dental professionals have a key role in both its identification and long-term management.